(3LGeY GdHjGf Yf JChjd Bi GdaQbGfs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3jHOC HJaSjQ ShQI GdaLQ HGdbhd ai JChjd bhdg YR hLd (B" (3hGdaLQ hdjGd YTQ (B" (3bGd CHh LYaQ CbSe QHfG Ld hYR HGdaLQ s
(3BNQgG (B:s
(3HfJgi HJaSjQ Chd ShQI Gdajd Hbhdg (B: (3hdh cGf bhdg dEjdGa bQjT ef UdI bhdg aLdYdg cYUa eCchd de Jcf Cde JQ s
(3HgG HJQ HYO GdhQbI (B50 (3CKfGA ShQI Gddjds
(3bWYI efg JTJed Ydi JaSjQ BjGJ ef ShQ GdaLQs
(3GdHdO s
(3GdTeS Gddjd s
(3Gdajd s
(3fSNI Ydi Qb ZRGd s
Keywords: (3GdJaSjQ hYdhe GdbQBfs